Effects of short-term concurrent training cessation on the energy cost of running and neuromuscular performances in middle-distance runners - Berryman, N.; Mujika, I.; Bosquet, L. (Sports, 2021)
Evidence supports the implementation of concurrent strength and running training, within the same mesocycle, to improve performances in middle- and long-distance events. However, very little is known about the effects of concurrent training cessation. The purpose of this investigation was to describe the effects of 4 weeks of explosive strength training cessation after an 8-week concurrent training protocol. Eight runners completed this study, which first included either plyometric (n = 4) or dynamic weight training (n = 4) in addition to the usual running regimen. Explosive strength training was thereafter interrupted for 4 weeks, during which running sessions were maintained. Participants were tested at baseline, after concurrent training and after concurrent training cessation. The results suggest that the energy cost of running improvements observed after the intervention (-5.75%; 95% CI = -8.47 to -3.03) were maintained once explosive strength training was interrupted (-6.31%; 95% CI = -10.30 to -2.32). The results also suggest that neuromuscular performances were maintained after 4 weeks of concurrent training cessation, especially when tests were specific to the training intervention. Furthermore, a 3000m time trial revealed a similar pattern, with improvements after the concurrent mesocycle (-2.40%; 95% CI = -4.65 to -0.16) and after concurrent training cessation (-4.43%; 95% CI = -6.83 to -2.03). Overall, only trivial changes were observed for aerobic endurance and V?O2peak. Together, these results suggest that short-term explosive strength training cessation might be beneficial and could be considered as a taper strategy for middle-distance runners. However, coaches and athletes must interpret these results cautiously considering the study`s low sample size and the very limited available literature in this domain.